Legal Protection Against The Implementation Of Policies For Deportation In The Border Areas Of Indonesia - Muhammad Ansor Lubis; Mahzaniar Mahzaniar (International Asia Of Law and Money Laundering (IAML), 2022)
Indonesia's constitution guarantees the right of citizens of Indonesia (WNI) to get a job and a decent livelihood in accordance with Article 27 Paragraph 2 of the 1945 constitution. The citizens also has the right to seek work anywhere as he wishes. This right cause migration of citizens abroad, especially to the neighboring Country, Malaysia. Unfortunately, many problems arise when they get in Malaysia which then resulted in a lot of citizens who should be deported to the border regions Nunukan Kalimantan Utara. Thus, this study aims to determine the form of the legal protection of the rights of Indonesian citizens who were deported in Kabupaten Nunukan in North Kalimantan Province. Specifically, the objectives are: (1) To determine the form of the legal protection of Indonesian citizens who were deported under the Labour LAW. This research is a legal research then approach the problem used is the method of approach to the law (statute approach), approach cases (cases approach), and a conceptual approach (conceptual approach). The approach of the law performed by means of studying the laws and regulations that still applies in particular in Kabupaten Nunukan in North Kalimantan Province are involved with legal issues. This approach is used to inventory and analyze the legal instruments of the national Indonesia for the rights of Indonesian citizens, especially the rights of Indonesian citizens who were deported. The results of this study are expected later able to provide input to the policy-setting protection strategies for deportan in the border region of Indonesia.